Racial Identification, Racial Discrimination, and Substance Use Vulnerability Among African American Young Adults - Stock, Michelle L. (Pers Soc Psychol Bull, 2011)
Two studies examined racial identity (RI) as a protective factor against substance use cognitions among African American young adults who either envisioned or experienced racial discrimination. In Study 1, participants envisioned a discrimination or nondiscrimination scenario, and then their willingness to use drugs and an indirect measure of substance use were assessed. Discrimination was associated with higher levels of use cognitions among participants with low levels of RI. In Study 2, participants were excluded or included in an online game (Cyberball) by White peers and then engaged in an RI-affirmation or control writing task. Participants attributed this exclusion to racial discrimination. Excluded participants who did not affirm their RI reported the highest levels of substance use cognitions, especially if they had engaged in higher levels of previous substance use. These findings highlight the importance of RI among Black young adults and the impact of discrimination on health behaviors.